Synthesis, electrical and electochemical studies of bismuth antimony oxide for ascorbic acid detection - Chia, Chew Theng (2017)
Oxide ion conductors have been studied widely for year due to its economic benefit in the application of solid fuel cell and further in chemically modified electrode for ascorbic acid detection. Bismuth oxide was a well-known good oxide ion conductor because of its crystal structure, which has high ratios of oxygen vacancies. Therefore, it was chosen in this studies. Bismuth antimony oxide ceramics, BixSb2Oδ where x=1.0, 1.5, 2.0 have been prepared by solid state method. The single phase of synthesized samples was confirmed by x-ray diffraction (XRD) analysis. The physico-chemical properties of synthesized samples were characterized. The elemental composition of each synthesized samples were in the acceptable range of ±5%. The results showed that the synthesized samples were thermally stable. Bi-O bonds were observed in FTIR for the synthesized samples. The SEM results showed that the porosity of the synthesized samples were reduced with the increasing in composition of bismuth. The electrical properties of synthesized samples were carried out using AC impedance spectroscopy. The conductivity of the synthesized samples is at the order of 10-7. The activation energy is in the range of 1.23-1.62 eV. The dielectric constant, ε’ is in the range of 23-28 and dielectric loss, tan δ is in the range of 10-2 at room temperature and frequency 1 MHz. Furthermore, the synthesized samples were used to study the electrochemical properties of the oxidation of ascorbic acid using cyclic voltammetry (CV). The powder of samples was attached onto the glassy carbon (GC) electrode. The oxidation current of ascorbic acid was enhanced by about 1.52 times by using modified electrode with 0.1 M potassium chloride as the supporting electrolyte. The optimum oxidation current of ascorbic acid was occurred in pH5. From the temperature studies, the activation energy is found to be 4.68 kJmol-1. The scan rate studies showed that a type of surface process was occurred. The calibration curve showed the sensitivity of modified electrode was closed up to 18 μA mM-1. The curve also can applied in the application of detection of vitamin C and commercial fruit juices.